Impact of second phase morphology and orientation on the plastic behavior of dual-phase steels. (July 2019) - Ismail, Karim; Perlade, Astrid; Jacques, Pascal J.; Pardoen, Thomas; Brassart, Laurence
Abstract: Martensite volume fraction, composition and grain size are the known primary factors controlling the mechanical behavior of ferrite-martensite dual-phase steels. Recently, excellent performances of dual-phase steels with a fibrous microstructure have been reported. However, the precise role of martensite morphology and orientation has not been thoroughly elucidated yet. This study develops a two-scale micromechanical modeling strategy in order to investigate the effect of particle morphology and orientation on the elastoplastic behavior of dual-phase steels. Finite element simulations are carried out on 3D periodic unit cells, each having a given orientation and volume fraction of spheroidal particles. The overall response is obtained by averaging the response of grains with different orientations, thus bypassing the need for costly full-field simulations on representative volume elements of realistic microstructures. A detailed parameter study systematically investigates the effect of particle morphology and orientation at grain level and at grain assembly level. While particle morphology and orientation effects lead to significant differences at grain level in terms of strain hardening behavior and back-stress development, the impact of the phase morphology at the homogenized multigrain level is almost negligible up to the onset of necking. However, the mechanical fields at the micro-scale are considerably influenced by both particle morphology and orientation, and are expected to largely impact the damage behavior through, among others, generating large grain-to-grain heterogeneities. Highlights: A two-level micromechanical model is proposed based on FE simulations on periodic unit cells representing grains. At grain level, particle aspect ratio and orientation significantly influence the plastic response. In contrast, particle aspect ratio has limited impact on the effective behavior of a randomly isotropic aggregate of grains. Particle aspect ratio and orientation considerably affect local mechanical fields, and hence damage and fracture behavior. A two-stage void coalescence process is suggested to explain the high fracture toughness observed in elongated microstructures.